The Effect of Investment Knowledge, Investment Risk, and Pocket Money on Interest in Investing in the Capital Market - Prabowo, Khabib Setyo; Nurdiwaty, Diah; Kurniawan, Andy (Universitas Nusantara PGRI Kediri, 2023)
Research Aim : The purpose of this study was to determine the effect of investment knowledge, investment risk and pocket money on students' interest in investing in the capital market. Research Method : This research was conducted through a quantitative approach using primary data obtained from 78 respondents, namely students from Nusantara University PGRI Kediri Faculty of Economics and Business who had received capital market lessons. Data analysis techniques in the form of descriptive statistics, classical assumption tests, Multiple Linear Regression Analysis, determinant coefficient and hypothesis testing. Research Finding : The results showed that investment knowledge had a significant positive effect on interest in investing in the capital market. Investment risk has no effect on interest in investing in the capital market. Pocket money has a significant positive effect on the interest in investing in the capital market. Based on the results of simultaneous testing, it is known that there is a significant positive effect between the variables of investment knowledge, investment risk, and pocket money with interest in investing in the capital market.